Is Post-Marketing Drug Surveillance Possible in the Family Practice Setting? A Collaborative Study - Facklam, David P. (1988)
Post-marketing surveillance is a mechanism to identify and quantify harmful, as well as beneficial, effects of drugs used under conditions different from those in which they were tested. The College of Family Physicians of Canada collaborated with the authors in a pilot, office-based, post-marketing, surveillance study. Target medications were selected from all prescriptions, written or authorized by participating physicians. The participants collected the prescriptions by using duplicate prescription pads. Follow-up data was collected from the patients by means of a self-administered questionnaire and from the physicians by means of a medical-chart review. This method of research allows the identification of a cohort of drug users in a systematic, non-biased fashion.